2020
DOI: 10.3390/ijerph17228522
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of Movement Restriction during the COVID-19 Outbreak on Clinical Undergraduates: A Cross-Sectional Study

Abstract: The COVID-19 pandemic has resulted in a Movement Control Order (MCO) in Malaysia and the subsequent closure of all educational institutions. We aimed to examine the psychological impact of the MCO among clinical undergraduates. A cross-sectional study was conducted using self-reported questionnaires that were distributed online using the Depression, Anxiety and Stress Scale-21 (DASS 21), Short Warwick Edinburgh Mental Well-Being Scale (SWEMWBS), and the newly designed MCO effect questionnaire. Seven hundred se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
81
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(106 citation statements)
references
References 29 publications
14
81
2
2
Order By: Relevance
“…A total of 20 samples and 13,960 respondents deriving from 15 studies [23,24,[28][29][30][31][32]35,37,38,40,41,43,45,47] reported in the presence and severity of depression. A variety of rating scales were used such as DASS-21 (60.0%), HADS (20%), and three other instruments (each 6.7%).…”
Section: The Pooled Prevalence Of Anxiety Depression and Insomniamentioning
confidence: 99%
“…A total of 20 samples and 13,960 respondents deriving from 15 studies [23,24,[28][29][30][31][32]35,37,38,40,41,43,45,47] reported in the presence and severity of depression. A variety of rating scales were used such as DASS-21 (60.0%), HADS (20%), and three other instruments (each 6.7%).…”
Section: The Pooled Prevalence Of Anxiety Depression and Insomniamentioning
confidence: 99%
“…Similarly, college students' anxiety and depression rates during the early stages of COVID-19 were not optimistic in the United States (Kecojevic et al, 2020 ) and Bangladesh (Khan et al, 2020 ). It is necessary and urgent to improve college students' mental status, and any exacerbation due to strict school regulations after school reopening is unacceptable (Giannopoulou et al, 2020 ; Kalok et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Malaysian Government has implemented the Movement Control Order (MCO) which aims to break the chain of COVID-19 in the population. The MCO prohibits mass gathering, stops international travel, and closes all academic and business premises except providers of essential services, including food, health, telecommunications, and transportation [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The public had to adapt to the new norm which includes wearing a face mask, social distancing, frequent hand washing, and avoiding mass gatherings [ 12 ]. The Malaysian government have been using multiple platforms to convey official information and updates on COVID-19 to the general population, which include daily press conferences, regular text messaging, and the use of social media [ 10 ].…”
Section: Introductionmentioning
confidence: 99%